A Chinese girl with neuromyelitis optica spectrum disorder coexisting with primary Sjogren’s syndrome: a case report and literature review - Zhu, Guo-qin; Hu, Rong-xuan; Peng, Yan; Yao, Yao; Li, Guo-min (Frontiers in Immunology, 2025)
IntroductionNeuromyelitis optica spectrum disorder (NMOSD) is an immune-mediated, typically relapsing central nervous system demyelinating disorder characterized by optic neuritis (ON) and transverse myelitis (TM). While systemic or organ-specific autoimmune comorbidities are well-documented in 20–30% of adult NMOSD cases, such associations remain rarely reported in pediatric populations.Case ReportWe present a 14-year-old girl with NMOSD coexisting with primary Sjögren’s syndrome (pSS). At 11 years of age, she presented with acute right-sided headache, painful eye movements, and vision loss. Diagnostic workup confirmed AQP4-IgG seropositivity, ON, and corresponding T2-hyperintense lesions on optic nerve MRI, meeting 2023 Neuromyelitis Optica Study Group (NEMOS) revised recommendations. Acute-phase treatment included intravenous methylprednisolone and intravenous immunoglobulin, followed by maintenance therapy with oral prednisone and mycophenolate mofetil (MMF), with gradual prednisolone tapering. Right-eye vision normalized after intervention. Initial workup revealed positive antinuclear antibody (ANA), anti-Ro/SSA, anti-La/SSB, and elevated alanine aminotransferase (ALT)/aspartate aminotransferase (AST). Aged 12.5 years, labial salivary gland biopsy for persistent transaminitis showed focal lymphocytic sialadenitis (focus score ≥1 focus/4 mm²), satisfying the 2016 ACR/EULAR criteria for pSS. At 13.5 years, MMF was switched to tacrolimus due to persistent ALT/AST elevation, leading to biochemical normalization. No NMOSD relapses occurred post-initial episode.ConclusionThis case highlights the rare but clinically important co-occurrence of NMOSD and pSS in children. Routine screening for autoantibodies (e.g., ANA, organ-specific antibodies) in pediatric NMOSD is warranted to detect comorbid autoimmune disorders. Targeted therapy for concurrent connective tissue diseases can optimize clinical outcomes and quality of life.